TiO2 structural support effects on the durability and recovery characteristics of proton exchange membrane fuel cell electrodes - Park, Jimin; Jo, Seunghyun; Kwon, Junhwa; Lee, Hena; Kweon, Do Hyung; Shin, Donghoon; Kim, Ohsub; Lim, Katie Heeyum; Seong, Jong Geun; Song, Kwang Ho; Jang, Jong Hyun; Park, Hee-Young (Elsevier BV, 2026)
Proton-exchange membrane fuel cells (PEMFCs) have already entered commercial use in the transportation sector; however, enhancing their durability remains a key requirement for enhancing their competitiveness against internal combustion engines. Among the various degradation mechanisms, cathode deterioration plays a decisive role, with carbon support corrosion being particularly detrimental because of irreversible structural collapse within the electrode. Although introduction of structural additives has been proposed as a strategy of mitigating such degradation, previous studies have been limited by the concurrent contribution of electronic or ionic conductivity to these additives, making it challenging to isolate the pure structural reinforcement effect. In this study, the authors employ a star-shaped TiO2 (ST) structure—an electrically and ionically low-conductive, corrosion-resistant material—to exclusively evaluate the structural stabilization effect on electrode degradation and durability. Gas chromatography analysis confirmed that the addition does not alter the extent of carbon corrosion. However, the ST-containing electrodes exhibited superior preservation of electrode thickness, pore structure, and capacitance compared to the cases in the reference electrode. As a result, the optimized ST electrode demonstrated more than twice the durability of the baseline electrode, while maintaining equal or higher initial performance. The findings demonstrate that not loss of conductivity but the structural collapse is the dominant factor limiting the durability of PEMFC under carbon corrosion conditions. Furthermore, this study is the first to experimentally isolate and quantify the pure structural stabilization effect using a low-conductive structural support, providing a design direction for next-generation durable PEMFC electrodes.